2016
DOI: 10.5505/tjtes.2016.83883
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative stool analysis for intestinal parasites and fecal occult blood in patients with acute appendicitis

Abstract: BACKGROUND: Etiology of acute appendicitis (AA) rarely involves parasitic infections of gastrointestinal (GI) tract. Preoperative diagnosis of parasitic infections in appendix remains difficult, although parasites can sometimes be observed inside the lumen during histopathological examination. The aim of the present study was to prospectively screen prevalence and species of intestinal parasites and adherence of fecal occult blood (FOB) in patients admitted to emergency department (ED) with clinical symptoms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Globally, E. vermicularis infection within the resected appendices in patients with symptoms of appendicitis ranging from 0.2% to 41.8% [23]. This percentage more likely suggested that the presence of E. vermicularis within the appendix lumen may result in symptoms "appendiceal syndrome" resembles acute appendicitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, E. vermicularis infection within the resected appendices in patients with symptoms of appendicitis ranging from 0.2% to 41.8% [23]. This percentage more likely suggested that the presence of E. vermicularis within the appendix lumen may result in symptoms "appendiceal syndrome" resembles acute appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…Within the resected appendix, the parasitic infections are generally an incidental finding and so on numerous parasites are found in the appendix lumen including protozoan parasites as E. histolytica, G. lamblia, B. coli, Cryptosporidium spp. and helminths as E. vermicularis [22,23].…”
Section: Discussionmentioning
confidence: 99%